MITIGASI PERUBAHAN IKLIM MELALUI KEGIATAN BELAJAR CERIA SAIN KONSERVASI LAHAN GAMBUT DI DESA HABARIN HURUNG PALANGKA RAYA - Santiani, Santiani; Supriatin, Atin; Annovasho, Jhelang; Azizah, Nadia; Haryono, Agus; Yuliani, Hadma; Mardaya, Mardaya; Fitriyani, Fitriyani (Universitas Padjadjaran, 2024)
Damage to peatlands causes greenhouse emissions which contribute to climate change. Climate change has impacted many aspects of human life. Mitigation of climate change must be carried out by all parties. Education is one aspect of mitigating climate change. Universities can be an example in developing programs or activities based on climate change mitigation. This PKM activity was carried out in Habarin Hurung Village, Palangka Raya City, Central Kalimantan in March 2022. This activity aimed to increase middle school students' understanding of peatlands and climate change. The PKM activity of learning cheerfully about the science of peatland conservation was carried out using a quasi-experimental research method with a one-group pretest-posttest design without a comparison group. The effectiveness of activities to increase the peatland environmental literacy of middle school students can be seen from hypothesis testing using a paired sample of 2 different tests assisted by SPSS 25. This activity produces posters made by secondary school students with the theme of peatlands and climate change. PKM activities to learn cheerfully about the science of peatland conservation effectively increase students' environmental and climate change literacy. The contents of the poster showed that students have been able to connect peatlands and global warming. Students' knowledge about peatlands and global warming is expected to foster environmentally caring behaviour. Similar activities should be carried out sustainably and with a wider community reach. Climate change mitigation activities can be carried out jointly by universities, schools and the community.Kerusakan lahan gambut menyebabkan emisi rumah kaca dan secara global akan menyebabkan perubahan iklim. Perubahan iklim telah berdampak pada banyak aspek kehidupan manusia. Mitigasi terhadap perubahan iklim harus dilakukan oleh semua pihak. Pendidikan menjadi salah satu aspek dalam mitigasi perubahan iklim. Universitas dapat menjadi contoh dalam pengembangan program atau kegiatan berbasis mitigasi perubahan iklim. Kegiatan PKM ini dilakukan di Desa Habarin Hurung, Kota Palangka Raya, Kalimantan Tengah pada bulan Maret 2022. Tujuan kegiatan ini untuk meningkatkan pemahaman siswa sekolah menengah tentang lahan gambut dan perubahan iklim. Kegiatan PKM belajar ceria sain konservasi lahan gambut dilakukan dengan metode penelitian quasi eksperimen dengan desain one group pre test-post test design tanpa kelompok pembanding. Efektivitas kegiatan untuk meningkatkan literasi lingkungan lahan gambut siswa sekolah menengah dilihat dari uji hipotesis dengan uji beda paired sample 2 test berbantuan SPSS 25. Kegiatan ini menghasilkan produk berupa poster yang dibuat siswa sekolah menengah dengan tema lahan gambut dan perubahan iklim. Kegiatan PKM belajar ceria sain konservasi lahan gambut efektif meningkatkan literasi perubahan iklim siswa. Isi poster menunjukkan bahwa siswa telah mampu menghubungkan lahan gambut dan pemanasan global. Pengetahuan siswa tentang lahan gambut dan pemanasan global diharapkan menumbuhkan perilaku peduli lingkungan. Kegiatan serupa sebaiknya dilakukan secara berkelanjutan dan dengan jangkauan masyarakat yang lebih luas. Aktivitas mitigasi perubahan iklim dapat dilakukan bersama oleh universitas, sekolah, dan masyarakat.